Monograf Persidangan Kolokium Penyelidikan Pelajar Pasca Siswazah Penyelidikan 2011 - UiTM, Faculty of Information Management (2011)
This colloquium is a knowledge sharing session that aims to inspire and provide encouragement and exposure to all postgraduate students in order to improve their performance and progress in their research.